PROBLEMS OF DEVIANT BEHAVIOR AMONG STUDENTS - N. Gerasimenko (Вестник университета)
The relevance of the study is in the changes that currently take place in all the spheres of modern Russian society and undermine the existing basis of life, disturb the equilibrium of the whole system. The greatest impact, and, above all negative, they have on the development of culture and spiritual life of young people. Currently, there is a tendency to «transform» education into a way of getting diplomas, high-paying job or a delay from the army, in other words, in a terminal value, which largely contributes to the development of specific deviations. The behavior of students during the learning process is closely linked with the importance of their higher education.